The Analysis of Self Leadership Strategies and Its Relationship with Psychological Empowerment Faculty Members at Emerging Saudi University - Aldighrir, Wafa Mohammed (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2019)
The present study aimed at understanding the relationship between self-leadership strategies and psychological empowerment of faculty members at Najran university. The sample of the study consists of around 340 faculty members who were randomly selected from among the faculty members concerned at one emerging university in Saudi Arabia for the academic year 2017/2018. Quantitative correlation and hierarchical regression methods were used to analyze the collected data. A survey questionnaire consisting of self-leadership strategies and psychosocial empowerment was created for the purpose of the study. The results revealed that natural reward strategies and constructive thought patterns, strategies showed a clear correlation with psychological empowerment among faculty members at Saudi Najran university. In contrast, behavior-focused strategies have shown no correlation with psychological empowerment among university faculty members. This article advises enhancing self-leadership and psychological empowerment among faculty members at Saudi emerging universities through training in leadership strategies in order to enhance overall faculty performance and encourage commitment to their university. Higher education institutions should encourage faculty members to set their own goals and focus on improving self-leadership strategies that enhance the psychological empowerment of faculty members, further aiding them to increase their effectiveness and productivity through their subsequent careers.